PENERAPAN E-LKPD PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN LITERASI DIGITAL PESERTA DIDIK KELAS X SMA - Maura Gita Cahyani; Winarsih; Pramita Yakub (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of learning in the digital era requires teachers to shift from being mere information transmitters to facilitators capable of creating interactive learning environments. However, the reality on the ground reveals that the majority of students still possess low levels of digital literacy, particularly regarding information retrieval and the critical evaluation of content. This issue extends to biology education, where the dominance of conventional teaching methods has hindered the optimal development of digital literacy skills. One instructional tool suitable for modern-era learning is the electronic student worksheet (E-LKPD). This study examines a learning approach utilizing E-LKPD—adapted from a version previously developed by Salsabila & Susantini (2022)—to enhance the digital literacy of 10th-grade students studying biodiversity. The research aims to describe: 1) the implementation of the lesson, 2) digital literacy skill activities, 3) learning outcomes (pre-test and post-test), and 4) student responses. Employing an applied research approach with a quasi-experimental design, the study involved 30 10th-grade students from SMAN 4 Sidoarjo. The measured parameters included lesson implementation, digital literacy skill activities, learning outcomes (pre-test and post-test), and student responses. Data were analyzed using quantitative descriptive techniques. The results indicate that: 1) the teacher's implementation of the lesson was excellent, achieving a score of 99.88%; 2) digital literacy skill activities reached 98.33%; 3) 91.15% of students performed excellently on assessments (pre-test and post-test) and met the required indicators of mastery; and 4) student response to the E-LKPD-based learning was 99.36%, indicating a highly positive reception. Based on these findings, the E-LKPD is effective as a learning medium for teaching biodiversity in biology.